(untitled) (Estudios de Historia de España, 2016)
The War of the Independence generated misery and ruin, increasing the material poverty and the decrease of the buying power of the population. Fruit of this negative economic context the town halls only could destine a tenth part of his budget to the welfare. The effects of the warlike contest against Napoleon also concerned the Church, institution that traditionally by means of diverse ecclesiastic organisations had to attend to the enormous social scarcities that were destroying to the village, since for example, to grant alms, attend to the patients in the hospitals, receive the orphans in the hospices or educate the youngest. In case of Lleida during the liberal regime the organization is necessary to emphasize of diverse meetings of charity, of health and of welfare destined to help the neediest.